Effects of grinding media on the surface roughness and flotation kinetics of lepidolite - Xu Zhang; Yan Zheng; Jingyi Li; Guangli Zhu; Guosheng Li; Yijun Cao (Results in Surfaces and Interfaces)
In this study, effects of ball and rod grinding on the surface roughness and flotation kinetics of lepidolite were investigated. Flotation tests revealed that the rod ground products had higher flotation efficiency than the ball ground products. The shape analysis showed the difference in roundness between the rod and ball ground products was very small. The AFM and BET results showed that the surface roughness of rod ground lepidolite was larger than that of ball ground lepidolite of the same grain size. The contact angle results showed that the rougher surface had stronger natural hydrophilicity and became more hydrophobic than smooth surface after dodecylamine treatment. The sum-frequency vibrational spectroscopy measurements showed that the rod ground lepidolite surface had good dodecylamine adsorption with a more compact and orderly arrangement. It is thus proposed that increasing surface roughness is conducive to the flotation performance of lepidolite using dodecylamine as a collector.